2001
DOI: 10.1021/ie000695c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cesium, Strontium, and Cobalt Ions on Magnetite and a Magnetite−Silica Composite

Abstract: Constant pH adsorption isotherms for nonradioactive Cs + , Sr 2+ , and Co 2+ on pure magnetite and a 80% (w/w) magnetite-silica composite were measured at 25 °C over a wide range of metal ion concentrations. The adsorption studies were carried out at four different pH's: 6, 7, 8, and 9 for Cs + and Sr 2+ and 5, 6, 7, and 8 for Co 2+ . All of the constant pH isotherms exhibited type I behavior with a saturation capacity that was pH-dependent and increased with increasing pH. The corresponding distribution coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 56 publications
2
54
0
2
Order By: Relevance
“…The value of K (mol/kJ) [2] is related to the adsorption mean free energy, E (kJ/mol), defined as the free energy change required to transfer 1 mole of ions from infinity in solution to the solid surface. The adsorption mean free energy E is given as E = (2K) Table 7.…”
Section: Dubinin-radushkevich Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of K (mol/kJ) [2] is related to the adsorption mean free energy, E (kJ/mol), defined as the free energy change required to transfer 1 mole of ions from infinity in solution to the solid surface. The adsorption mean free energy E is given as E = (2K) Table 7.…”
Section: Dubinin-radushkevich Isothermsmentioning
confidence: 99%
“…The radionuclide 137 Cs is produced in high yield during the fission process and due to its long half-life (T 1/2 = 30.17 yr) and its high solubility in aqueous media, it is a principal radiocontaminant in radioactive wastes [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…About adsorption capacity, Ebner et al [27] reported that the maximum adsorption capacity of Cs(II) on magnetite was 0.187 mg/g at pH 6.0. So, the sorbent developed in the present study exhibits higher adsorption capacity compared to other sorbents.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…The factor of separation of Langmuir, R L, which is an essential factor characteristic of this isotherm is calculated by using the relation [15]:…”
Section: The Langmuir Isothermmentioning
confidence: 99%